Chemical mechanical polishing pad

By introducing non-reactive non-expanded polymer particles and a small number of expanded polymer microspheres into the chemical mechanical polishing pad to form a semi-moon-shaped opening polishing pad, the problems of reduced flatness and poor processing properties of existing polishing pads during the polishing process are solved, and more efficient polishing effect and better processing performance are achieved.

JP2025058929APending Publication Date: 2025-04-09DUPONT ELECTRONIC MATERIALS HLDG INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024148253
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-27
Filing Date
2024-08-30
Publication Date
2025-04-09

AI Technical Summary

Technical Problem

The existing chemical mechanical polishing pads are prone to decrease in flatness due to porous properties during the polishing process, and are difficult to process into a desired macromicrostructure.

Method used

A polymer polishing pad containing 1-20% by weight non-reactive non-expanded polymer particles and less than 2% by weight expanded polymer microspheres, the polishing pad with this configuration showed a half-moon opening under SEM observation, enhancing the mechanical properties and processability of the polishing pad.

Benefits of technology

Improve the flatness and processability of the polishing pad, enhance the adaptability to the matrix, and reduce the inhomogeneity and residues during the polishing process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025058929000001_ABST
    Figure 2025058929000001_ABST
Patent Text Reader

Abstract

To provide a chemical mechanical polishing pad that can be more easily cut and machined to impart desired macro- and micro-textures.SOLUTION: A chemical mechanical polishing pad includes a polishing layer that includes a matrix polymer 22, 1 to 20 weight% of non-reactive non-expanding polymer particles dispersed in the matrix polymer, and less than 2 weight% of expandable polymer microspheres, on the basis of the total weight of the polishing layer. The SEM of a cross-section of the polishing layer shows a crescent-shaped opening adjacent to and separating the surface of at least a portion of the polymer particle from the matrix polymer.SELECTED DRAWING: Figure 4
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polishing pad for chemical mechanical polishing. [Background technology]

[0002] In the manufacture of integrated circuits and other electronic devices, multiple layers of conductive, semiconductive, and dielectric materials are deposited on and removed from the surface of a semiconductor wafer. Thin layers of conductive, semiconductive, and dielectric materials can be deposited using a number of deposition techniques. Common deposition techniques in current wafer processing include physical vapor deposition (PVD), also known as sputtering, chemical vapor deposition (CVD), plasma-enhanced chemical vapor deposition (PECVD), and electrochemical plating, among others. Common removal techniques include wet and dry isotropic and anisotropic etching, among others.

[0003] As layers of material are successively deposited and removed, the top surface of the wafer becomes uneven. Subsequent semiconductor processing (e.g., metallization) requires that the wafer have a flat surface, so the wafer must be planarized. Planarization is useful for removing undesirable surface features and surface defects, such as rough surfaces, agglomerated materials, crystal lattice damage, scratches, and contaminated layers or materials.

[0004] Chemical mechanical planarization, or chemical mechanical polishing (CMP), is a common technique used to planarize or polish workpieces such as semiconductor wafers. In conventional CMP, a wafer carrier, or polishing head, is mounted on a carrier assembly. The polishing head holds the wafer and positions it in contact with a polishing layer of a polishing pad mounted on a table or platen in the CMP apparatus. The carrier assembly provides a controllable pressure between the wafer and the polishing pad. At the same time, a polishing medium (e.g., a polishing liquid or slurry) is dispensed onto the polishing pad and drawn into the gap between the wafer and the polishing layer. For the purposes of this application, a polishing liquid means a polishing liquid with or without particles, and a polishing slurry means a polishing liquid with particles. To perform the polishing, the polishing pad and wafer typically rotate relative to one another. As the polishing pad rotates under the wafer, the wafer typically sweeps an annular polishing track, or polishing area, where the surface of the wafer is directly opposed to the polishing layer. The wafer surface is polished and planarized by the chemical and mechanical action of the polishing layer and the polishing medium on the surface.

[0005] Chemical mechanical polishing pads often contain grooves cut into the polishing surface. These grooves are considered a macrotexture and can improve the performance of the pad. For example, the grooves can facilitate removal of debris from the polishing surface that could otherwise damage the surface. Additionally, polishing pads can include a microtexture. See, for example, U.S. Patent No. 5,399,933, which describes pads with macrotexture and microtexture.

[0006] In some cases, the polishing layer can be made porous, for example by including expandable polymer microspheres in the polishing layer. This porosity can impart a microtexture to the polishing surface of the pad. When the pad is conditioned by the abrasive during patterned wafer polishing, the abrasion of the polymer material exposes the pores, forming the microtexture. See, for example, FIG. 1.

[0007] However, a porous pad may provide less effective planarization because the pad may conform too closely to variations in height of the substrate being polished. For example, as shown in FIG. 2, a substrate 10 being polished includes raised features 11. A porous polishing pad 20 having pores 21 in a matrix polymer 22 may deform under the pressure of polishing. In addition, a porous pad may cause dishing of the substrate.

[0008] Although unfilled non-porous pads can provide improved stiffness during polishing over porous pads, certain soft or ductile materials used in the polishing layer can be difficult to machine into pads with the desired macro-texture. As shown in Figure 3A, there may be a lack of uniformity in the grooves and spacing. Additionally, there may be rough edges and debris, as shown in Figures 3A and 3B. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] U.S. Pat. No. 5,489,233 Summary of the Invention [Problem to be solved by the invention]

[0010] It would be desirable to provide a pad that offers improved planarization capabilities over porous pads and that can also be more easily cut and machined to impart desired macro- and micro-textures. [Means for solving the problem]

[0011] Provided herein is a chemical mechanical polishing pad having an abrasive layer, the abrasive layer comprising a matrix polymer, 1-20 wt % non-reactive non-expanding polymer particles dispersed in the matrix polymer, and less than 2 wt % expandable polymer microspheres, based on the total weight of the abrasive layer, wherein SEM of a cross-section of the abrasive layer shows a crescent-shaped opening adjacent to and separating a surface of at least a portion of the polymer particle from the matrix polymer.

[0012] Reference will now be made to the exemplary embodiments, in which like elements are numbered like figures, and in which: [Brief description of the drawings]

[0013] [Figure 1] 1 is a scanning electron microscope (SEM) photograph at 200x magnification showing the surface of a porous polishing pad with expanded polymeric microspheres after polishing. [Diagram 2] 1 is a cross-sectional schematic diagram of a porous polishing pad polishing a substrate having raised surface features. [Figure 3A-3B] 1 is a photograph showing grooves on the surface of a comparative unfilled polishing pad. [Figure 4] 1 is a cross-sectional schematic diagram of a polishing pad disclosed herein polishing a substrate having raised surface features. [Diagram 5] 5 is a SEM at 500x magnification of a cross-section of the polishing layer of a polishing pad disclosed herein. [Figure 6] 5 is a SEM at 500x magnification of a cross-section of the polishing layer of a polishing pad disclosed herein. [Figure 7] 1 is a 500x magnification SEM of a cross-section of a prior art polishing pad having a polishing layer that includes expanded polymeric microspheres to impart porosity. [Figure 8] 500x SEM of the post-polishing surface of a pad disclosed herein. [Figure 9] 1 is an SEM of the post-polishing surface of a pad containing expandable polymeric microspheres. [Figure 10A-10B]3 is a photograph showing grooves on the surface of a polishing pad disclosed herein. [Figure 11] 13 is a photograph showing an attempt at a circular groove pattern on a pad by Comparative Sample D. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The polishing pads disclosed herein comprise particles in a matrix polymer.

[0015] The matrix polymer may be polyurethane. The matrix polymer has a melting point of 140×10 in the temperature range of 20° C. to 150° C. -6 Or 150 x 10 -6 Above and 250 x 10 -6 , 200×10 -6 , 180×10 -6 , or 170 x 10 -6 The matrix polymer may have a coefficient of thermal expansion (CTE) of up to millimeter / millimeter of original length of the sample / °C (mm / mm-°C). The matrix polymer may be ductile. The matrix polymer may have a contact angle with water and organic liquids of 36 millijoules per square meter (mJ / m 2 )~39mJ / m 2 The matrix polymer may have a Shore D hardness according to ASTM D2240-15(2015) of 30 to 80, typically 50 to 80. The matrix polymer may exhibit a wet Shore D hardness that is 5% or 10% up to 20% lower than the (dry) Shore D hardness of the matrix polymer.

[0016] For example, a polyurethane may be the reaction product of a mixture including a curing agent, such as one or more polyamine or polyol curing agents, and a polyisocyanate prepolymer (or a blend of two or more polyisocyanate prepolymers).

[0017] The polyisocyanate prepolymer may comprise the reaction product of components including a polyfunctional isocyanate and a prepolymer polyol, and optionally also including a low molecular weight polyol.

[0018] The polyfunctional isocyanate may be an aliphatic polyfunctional isocyanate, an aromatic polyfunctional isocyanate, or a mixture thereof. The polyfunctional isocyanate may be a diisocyanate, such as 2,4 toluene diisocyanate; 2,6 toluene diisocyanate; 2,2' diphenylmethane diisocyanate; 2,4' diphenylmethane diisocyanate; 4,4' diphenylmethane diisocyanate; naphthalene 1,5 diisocyanate; toluidine diisocyanate; paraphenylene diisocyanate; xylylene diisocyanate; isophorone diisocyanate; hexamethylene diisocyanate; 4,4' dicyclohexylmethane diisocyanate; cyclohexane diisocyanate; or a mixture of two or more thereof. The polyfunctional isocyanate may be toluene diisocyanate.

[0019] The prepolymer polyol can be selected from the group consisting of diols, polyols, polyol diols, copolymers thereof, and mixtures thereof. The prepolymer polyol can be selected from the group consisting of polyether polyols (e.g., poly(oxytetramethylene) glycol, poly(oxypropylene) glycol, poly(oxyethylene) glycol, poly(oxypropylene)-co-poly(oxyethylene) glycol); polycarbonate polyols; polyester polyols; polycaprolactone polyols; mixtures thereof. The prepolymer polyol can be, for example, polytetramethylene ether glycol (PTMEG), polypropylene ether glycol (PPG), polyethylene ether glycol (PEG), polyethylene ether glycol-co-polypropylene ether glycol (PEG-PPG copolymer), or a mixture of two or more thereof. For example, the prepolymer can be a blend of PPG and PTMEG in a weight ratio of PPG:PTMEG of 1:20 or 1:15 to 20:1, 10:1, 5:1, 1:1, or 1:10.

[0020] The low molecular weight polyol may be, for example, ethylene glycol; 1,2 propylene glycol; 1,3 propylene glycol; 1,2 butanediol; 1,3 butanediol; 2 methyl 1,3 propanediol; 1,4 butanediol; neopentyl glycol; 1,5 pentanediol; 3 methyl 1,5 pentanediol; 1,6 hexanediol; diethylene glycol; dipropylene glycol; or tripropylene glycol.

[0021] The polyisocyanate prepolymer can have an unreacted isocyanate (NCO) concentration of 7 to 11.4, 8 to 10, 8.3 to 9.8, 8.5 to 9.5, 8.6 to 9.3, 8.7 to 9.25, or 8.9 to 9.25 weight percent, based on the total weight of the isocyanate-terminated urethane prepolymer. Examples of commercially available isocyanate terminated urethane prepolymers include Imuthane® prepolymers (available from COIM USA, Inc., e.g., PET80A, PET85A, PET90A, PET93A, PET95A, PET60D, PET70D, PET75D); Adiprene® prepolymers (available from LANXESS Urethane Systems, e.g., LF800A, LF900A, LF910A, LF930A, LF931A, LF939A, LF950A, LF952A, LF600D, LF601D, LF650D, LF667, LF700D, LF750D, LF751D, LF752D, LF753D, L325); Andur® prepolymers (available from Anderson Development Available from the Company, for example, 70APLF, 80APLF, 85APLF, 90APLF, 95APLF, 60DPLF, 70DPLF, 75DPLF).

[0022] The aromatic diisocyanate, such as toluene diisocyanate, may be present in the reaction mixture in an amount, for example, from 33% or 35% to 46% or 45% by weight, based on the total weight percent of reactants used to make the polyisocyanate prepolymer.

[0023] The optional low molecular weight polyol may be present in the reaction mixture in an amount of from 1 or 3% to 12 or 11% by weight, based on the total weight of reactants used to make the polyisocyanate prepolymer.

[0024] To form the abrasive, a mixture is prepared that includes from 65%, 70%, or 75% by weight to 80%, 79%, or 78% by weight of polyisocyanate prepolymer and from 15%, 20%, or 20% by weight to 30%, 27.5%, or 25% by weight of a curing agent, based on the total weight of the mixture. The mixture also includes non-reactive non-expanding polymer beads in an amount of from 1%, 3%, 5%, 6%, 7%, or 8% by weight to 20%, 15%, 14%, or 12% by weight, based on the total weight of the mixture. For purposes of this specification, expandable polymer beads expand in diameter by more than 5% when heated above the glass transition temperature, and non-expandable polymer beads expand in volume by less than 1% when heated above the glass transition temperature.

[0025] The stoichiometric ratio of the sum of the total moles of amine (NH2) groups and the total moles of hydroxyl (OH) groups in the hardener mixture to the total moles of unreacted isocyanate (NCO) groups in the reaction mixture ranges from 0.85:1, or 0.91:1, or 0.95:1, or 0.98:1, to 1.15:1, or 1.10:1, or 1.05:1. Polyurethane reaction products can be formed from reaction mixtures including polyisocyanate prepolymers and hardener mixtures in which the molar ratio of polyamine NH2 groups to polyol OH groups ranges from 2:1, or 4:1, or 25:1, or 50:1, to 1:0 or pure amine (when the molar ratio is 1:0, there are no OH groups remaining in the hardener mixture) or 70:1.

[0026] The polyisocyanate prepolymers can have a number average molecular weight (GPC) of, for example, from 500 or 600 to 2000, 1500, 1200, or 1000 grams per mole (g / mol).

[0027] The curing agent may be a polyamine, a polyol, or a mixture of polyamines and polyols. Examples of polyamine curing agents include 4,4'-methylene-bis(3-chloro-2,6-diethylaniline) or 4,4'methylenebis(2chloroaniline); diethyltoluenediamine; tert-butyltoluenediamine such as 5-tert-butyl-2,4- or 3-tert-butyl-2,6-toluenediamine; chlorotoluenediamine; dimethylthio-toluenediamine; 1,2-bis(2-aminophenylthio)ethane; trimethylene glycol di-p-amino-benzoate; 5-tert-amyl-2,4- and 3-tert-amyl-2, Examples of suitable curing agents include tert-amyltoluene diamines such as 6-toluene diamine, tetramethylene oxide di-p-aminobenzoate, (poly)propylene oxide di-p-aminobenzoate, chlorodiaminobenzoate, methylene dianiline such as 4,4'-methylene-bis-aniline, isophorone diamine, 1,2-diaminocyclohexane, bis(4-aminocyclohexyl)methane, 4,4'-diaminodiphenylsulfone, m-phenylenediamine, xylylene diamine, 1,3-bis(aminomethylcyclohexane), and mixtures thereof. For example, the amine curing agent may be 4,4'-methylene-bis-o-chloroaniline. Examples of polyol curing agents include ethylene glycol; 1,2 propylene glycol; 1,3 propylene glycol; 1,2 butanediol; 1,3 butanediol; 2 methyl 1,3 propanediol; 1,4 butanediol; neopentyl glycol; 1,5 pentanediol; 3 methyl 1,5 pentanediol; 1,6 hexanediol; diethylene glycol; dipropylene glycol; or tripropylene glycol; Specflex® polyols, Voranol® polyols, and Voralux® polyols (available from The Dow Chemical Company); Multranol® Specialty Polyols, and Ultracel® Flexible Polyols (available from Covestro AG); and Pluracol® Polyols (available from BASF).

[0028] The mixture includes polymer beads that do not react and do not expand substantially during the reaction and formation of the polishing material (i.e., are not considered expandable particles from trapped gas or liquid). The polymer beads can be substantially non-porous or have some porosity. Pads containing beads with some porosity can be more easily machined and conditioned. Non-porous beads can have a density of, for example, about 1.1 to 1.2 or 1.15 to 1.18 grams per cubic centimeter (g / cc), although the density can vary depending on the specific polymer selected. Porous beads can have a density to a value lower than the density of non-porous beads (e.g., less than 1.1, less than 1.15, or less than 1.18). For example, porous beads can have a density of from 0.75 g / cc or from 0.8 g / cc to 1.1 g / cc, 1.0 g / cc, or 0.95 g / cc.

[0029] For example, polymer beads have a melting point of 120×10 in the temperature range of 20°C to 150°C. -6 For example, 70×10 -6 From 120×10 -6 , 100×10-6, or 90×10 -6 The polymer beads can have a coefficient of thermal expansion (CTE) of up to 40 mJ / m2, derived from contact angles with water and various organic liquids. 2 ~43mJ / m 2 The bead may have a surface energy at 20°C of 0.01 to 0.01 mm / mm°C. Without wishing to be bound by theory, the difference in CTE or surface energy between the matrix polymer and the beads may contribute to the unique properties and effectiveness of the polishing pads disclosed herein. For example, the CTE of the polymer beads may be at least 30, or at least 40, or at least 50 mm / mm°C less than the CTE of the polyurethane matrix.

[0030] The polymer beads can include, for example, crosslinked (meth)acrylate polymers or non-crosslinked (meth)acrylates, polyolefins such as polyethylene, polypropylene, or olefin copolymers, polylactic acid (PLA), polylactic-co-glycolic acid (PLGA), polysiloxanes, or cellulose polymers. Advantageously, the polymer beads have a higher elastic modulus than the polymer matrix. The combination of the lack of chemical bonds between the polymer beads and the polymer matrix and the high elastic modulus contributes to the release of particles when conditioning the polishing pad with an abrasive such as diamond abrasive.

[0031] The polymeric beads may have an average particle size D50 as measured by a particle size analyzer of less than 20 micrometers, for example, greater than 2 micrometers, at least 3 micrometers, at least 6 micrometers, at least 7 micrometers, at least 8 micrometers, at least 9 micrometers, at least 10 micrometers, up to 20 micrometers, up to 18 micrometers, up to 15 micrometers, up to 14 micrometers, up to 13 micrometers, or up to 12 micrometers. For the purposes of this application, D50 represents the equivalent particle size of the 50th percentile by cumulative population. The equivalent particle size represents the equivalent size to the diameter of a spherical particle of the same volume.

[0032] The polymer beads can impart a unique morphology to the pad. For example, as shown in Figures 5 and 6, a crescent-shaped gap 50 is seen between the surface of the polymer beads 60 and the polymer matrix 70 on a surface cut with a sharp instrument. With reference to Figures 5 and 6, the crescent shape refers to the gap 50 formed between the polymer beads 60 and the polymer matrix 70 in an SEM at a magnification of at least 500 times using a microtome blade with a microtome and polymer matrix at room temperature or 20°C. Typically, the microtome blade moves the polymer beads 60 in the cutting direction, moving the polymer beads 60 against the wall of the polymer matrix 70 on the opposite side of the initial blade contact. The typical spacing between the polymer beads 60 and the polymer matrix 70 is at least 0.1 μm and ranges from 0.1 μm to 7 μm, as measured by the polymer beads 60 remaining in the polymer matrix 70 after cutting the polymer beads 60 with a microtome at a diameter of at least 50 percent of the average diameter. Most advantageously, this distance is 0.2 to 5 μm. Furthermore, this measurement is most favorable for spherical polymer beads 60 where the polymer beads 60 are in contact or near contact with the sidewall of the polymer matrix 70 that is on the opposite side of the measured distance. This movement of the polymer beads 60 when cut with a microtome is believed to be due to the polymer beads 60 having weak or no bonds securing them to the polymer matrix 70.

[0033] The beads in FIG. 5 are somewhat porous, whereas the beads in FIG. 6 are non-porous. In contrast, in FIG. 7, a cut surface of an abrasive material having the same polymer matrix material 70 as the material shown in FIG. 5, but including expandable polymer microspheres 80, shows a clear morphology. Furthermore, the polymer beads are removed or released from the surface during conditioning, leaving depressions 10 on the surface, such as hemispherical depressions as shown in FIG. 8. These depressions 10 are advantageously hemispherical. Furthermore, conditioning, such as diamond conditioning, creates fine channels in the polymer matrix. The hemispherical depressions combined with the fine channels form the microtexture of the polishing layer of the polishing pad. In contrast, pads used with expandable polymer microspheres also show depressions, but they often include shells of polymer microspheres, as shown in FIG. 9, where a residual shell 90 can be seen.

[0034] Advantageously, the polishing pad contains less than 2% by weight of expandable polymeric microspheres. Most advantageously, the polishing pad contains less than 1% by weight of expandable polymeric microspheres. The mixture used to manufacture the abrasive can be free or substantially free of expandable polymeric microspheres. By substantially free, it is meant that the mixture contains less than 0.2%, less than 0.1%, less than 0.05%, or less than 0.01% by weight of expandable polymeric microspheres based on the total weight of the mixture. The mixture can contain polytetrafluoroethylene or other fluoropolymer particles having an average diameter of 3 to 75 micrometers in an amount of 0% or less than 0.1% by weight based on the total weight of the mixture.

[0035] The abrasive can be formed by combining a polyisocyanate prepolymer, a hardener, and polymer beads in a mixture under reactive conditions. For example, this can include preparing a mold; pouring the mixture of reactants and polymer beads into the mold; and reacting the mixture in the mold to form a cured cake; and the abrasive layer is obtained from the cured cake. For example, the mixture can be prepared by preparing a polyisocyanate prepolymer at a temperature of, for example, 45-65°C, cooling the prepolymer to 20-40°C, and forming a reaction mixture of the polyisocyanate prepolymer, the hardener, and the polymer beads. Further, the method can include preheating the mold from, for example, 60°C or 65°C to 100°C or 95°C, filling the mold with the reaction mixture, and heating and curing the mixture at a temperature of 80-120°C for 4 hours or 6 hours to 24 hours or 16 hours to form a molded polyurethane reaction product. The cured cake can be scraped (cut) to obtain multiple abrasive layers from a single cured cake. The abrasive layers so cut can have a thickness of from 0.5 mm or 1 mm to 10 mm, 5 mm, or 3 mm. Optionally, the method further comprises heating the hardened cake to facilitate the scraping operation. Optionally, the hardened cake is heated using infrared heat lamps during the scraping operation in which the hardened cake is scraped into the multiple abrasive layers.

[0036] The abrasive layer has a density of at least 1.08 or at least 1.10 grams per cubic centimeter. The abrasive layer can have a density of up to 1.2 or 1.15 grams per cubic centimeter. Density can be determined by measuring the weight and volume of a sample and dividing the weight by the volume.

[0037] The polishing layer of the chemical mechanical polishing pad of the present invention exhibits a Shore D hardness of 55 to 75 measured according to ASTM D2240-15 (2015). These hardness values ​​were measured using a Hoto Instruments Asker P2 durometer equipped with a D probe by stacking four 3.81 cm square samples having a thickness of 80 mils (2.032 mm) to eliminate errors in measuring the support surface. Polishing layers with a Shore D hardness of less than 40 typically have very high elongation to break values ​​(i.e., greater than 600%). Materials exhibiting such high elongation to break values ​​are reversibly deformed when subjected to machining operations, resulting in unacceptably poor groove formation and poor texture formation during diamond conditioning. Preferably, the polishing layer of the chemical mechanical polishing pad of the present invention exhibits an elongation at break of 100-450%, or preferably 125-425% (more preferably 150-350%, most preferably 250-350%), as measured according to ASTM D412-06a (2006). The test used an MTS Criterion C43 tester equipped with an Instron 2712-02 load cell with a maximum load of 1000 Newtons and Instron pneumatic side action grips clamping at approximately 30 psi (207 kPa). The specimens were based on the dimensions of a standard dumbbell die C in U.S. customary units with a thickness of 80 mils (2.032 mm), and the test temperature was 23°C + / - 2°C. The specimens were deformed with the grips at 20 inches (50.8 cm) + / - 2 inches per minute (5.08 cm / min). Five replicates were measured for each sample, and the median was reported.

[0038] Preferably, the polishing layer used in the chemical mechanical polishing pad of the present invention has an average thickness of 500 to 3750 microns (20 to 150 mils), more preferably 750 to 3150 microns (30 to 125 mils), even more preferably 1000 to 3000 microns (40 to 120 mils), and most preferably 1250 to 2500 microns (50 to 100 mils).

[0039] The chemical mechanical polishing pad of the present invention optionally further comprises at least one additional layer bonded to the polishing layer at an interface. For example, the chemical mechanical polishing pad optionally further comprises a compressible subpad or base layer bonded to the polishing layer. The compressible base layer preferably improves the conformability of the polishing layer to the surface of the substrate being polished.

[0040] The polishing layer of the chemical mechanical polishing pad of the present invention has a polishing surface suitable for polishing a substrate. The polishing surface has a macrotexture. The macrotexture may be grooves, recessed features, or raised features. The macrotexture may have a depth dimension of about 10%-60% (e.g., 50-2250 microns) of the thickness of the polishing layer and a width dimension of 250-1270 microns (about 10 mils-50 mils). For example, the macrotexture may include at least one of holes and grooves. The holes may extend from the polishing surface through or throughout the thickness of the polishing layer. The grooves are disposed on the polishing surface such that as the chemical mechanical polishing pad rotates during polishing, at least one groove sweeps the surface of the substrate being polished. For example, the polishing layer may have a macrotexture including at least one groove selected from the group consisting of curved grooves, linear grooves, holes, and combinations thereof.

[0041] As a specific example, the macrotexture can be a groove design including a plurality of grooves. The groove design can be concentric grooves (which may be circular or spiral), curved grooves, radial grooves, cross-hatch grooves (e.g., arranged as an XY grid across the pad surface), other regular designs (e.g., hexagons, triangles), tire tread-type patterns, irregular designs (e.g., fractal patterns), or combinations thereof. The groove shape is preferably selected from rectangular shapes with straight sidewalls, or the cross section of the groove can be "V" shaped, "U" shaped, sawtooth, and combinations thereof.

[0042] The macro-texture (eg, grooves) may be cut into the polishing surface of the polishing pad using either a lathe or a CNC milling machine.

[0043] The polishing layers disclosed herein can be easily machined to provide a defect-free macrotexture. For example, as shown in Figures 10A and 10B, the walls of the grooves machined into the surface of the polishing layer can be straight or smoothly curved without any significant defects in the walls or grooves.

[0044] The chemical mechanical polishing pads described herein can be used to polish a substrate. In particular, the method includes preparing a substrate to be polished and preparing a polishing pad described herein. The polishing pad is first conditioned before starting polishing of the substrate with the polishing pad. Additionally, the polishing pad can be further conditioned during intermittent interruptions in the polishing process (ex situ). The intermittent interruptions can occur during polishing of a single substrate or between polishing of a first substrate and a second substrate. Conditioning can include mechanically polishing the surface, for example, with a conditioning disk. The conditioning disk typically has a rough conditioning surface comprised of embedded diamond points. The conditioning process cuts fine grooves into the surface of the pad, abrading and plowing the pad material and renewing the polishing texture. The conditioning disk can rotate in a fixed position relative to the axis of rotation of the polishing pad, sweeping an annular conditioning area as the polishing pad rotates.

[0045] The substrate being polished may be a magnetic substrate, an optical substrate, or a semiconductor substrate. As a specific example, the substrate may be a substrate having small feature sizes. As another specific example, the substrate may be an advanced logic chip. The methods described herein are particularly useful for planarizing such substrates without forming substantial undesirable dishing on the substrate being polished.

[0046] Preferably, the method of polishing a substrate of the present invention includes providing a substrate selected from at least one of a magnetic substrate, an optical substrate, and a semiconductor substrate (preferably a semiconductor substrate such as a semiconductor wafer), providing a chemical mechanical polishing pad as disclosed herein, providing a polishing liquid between the polishing pad and the substrate, creating dynamic contact between the polishing surface of the polishing layer and the substrate to polish a surface of the substrate, and conditioning the polishing surface with an abrasive conditioner during one or more intermittent pauses during polishing.

[0047] 4, the substrate 10 being polished includes raised features 11. A polishing pad 30 including polymer beads 31 in a matrix polymer 22 does not substantially deform under the pressure of polishing into the areas between the raised features 11. EXAMPLES

[0048] Example Set 1 Polishing pads were fabricated with the same polyurethane matrix polymer and various non-reactive additives as shown in Table 1. They were used to polish substrates and evaluated for dishing. A set of SKW 3-2 300 mm wafers patterned with CVD oxide from SKW Associates, Inc. was used for polishing. The top oxide surface was removed by polishing and stopping at the Si3N4 layer, and then the lost height of the trench oxide was measured by a Brucker atomic force microscope (AFM) at six locations with different feature sizes: 500 μm × 500 μm, 250 μm × 250 μm, 100 μm × 100 μm, 50 μm × 50 μm, (trench width and land width), 30% density (high area 30 μm / low area 70 μm), and 70% density (high area 70 μm / low area 30 μm). An overpolish of 15% beyond endpoint detection was used. Additionally, pads fabricated from polishing layers 1, A, B, and C were evaluated for defects by examining chatter marks at high downforce (HDF, 170 hPa) and low downforce (LDF, 120 hPa) based on the stress exerted across the surface area of ​​the polished substrate. The pads were conditioned ex situ (i.e., during a pause in polishing the substrate). The results are shown in Table 1.

[0049] Example Set 2 A second set of polishing pads was fabricated using the same polyurethane matrix polymer as Example Set 1 and various non-reactive additives as shown in Table 2 and used for polishing as in Example Set 1, except that polishing was continued to 30% overpolish after endpoint detection. This additional overpolish resulted in more severe dishing. However, Samples 1-2 containing PMMA beads still had lower dishing than Comparative Sample A containing expandable polymer microspheres. Comparative Sample D showed significantly better dishing results, but it was not possible to machine the sample without severe defects, as shown in FIG. 11.

[0050] Example Set 3 A third set of polishing pads was manufactured using the same polyurethane matrix polymer as Example Set 1 with various non-reactive additives as shown in Table 3, where "7 / 3" indicates a line width of 7 microns and a space width of 3 microns. These were used to polish 8 inch (20.3 cm) tungsten patterned wafers. The results are shown in Table 3.

[0051] [Table 1]

[0052] [Table 2]

[0053] [Table 3]

[0054] Combining Tables 1-3 shows that PMMA polymer beads provide improved tungsten removal rates while providing equal or improved dishing, equal or improved defectivity. 3 wt. % expandable polymer microspheres increase chatter marks compared to the PMMA polymer beads of the present invention.

[0055] The present disclosure further includes the following aspects.

[0056] Aspect 1. A chemical mechanical polishing pad having an abrasive layer, the abrasive layer comprising a matrix polymer, 1-20 wt. % non-reactive non-expanding polymer particles dispersed in the matrix polymer, and less than 2 wt. % expandable polymer microspheres, based on the total weight of the abrasive layer, wherein an SEM of a cross-section of the abrasive layer shows a crescent-shaped opening adjacent to and separating a surface of at least a portion of the polymer particle from the matrix polymer.

[0057] Aspect 2. The chemical mechanical polishing pad of aspect 1, wherein the non-reactive non-swelling polymer particles comprise crosslinked polymethyl methacrylate.

[0058] Aspect 3. The chemical mechanical polishing pad of aspect 1 or 2, wherein the non-reactive non-swelling polymer particles have an average particle size D50 particle size of 5 to 15 microns.

[0059] Aspect 4. The chemical mechanical polishing pad according to any one of Aspects 1 to 3, wherein the matrix polymer is ductile.

[0060] Aspect 5. The chemical mechanical polishing pad of any one of aspects 1 to 4, wherein the matrix polymer is a polyurethane comprising a reaction product of an isocyanate-terminated prepolymer and an amine curing agent, the isocyanate-terminated prepolymer comprising the reaction product of a polyol prepolymer, toluene diisocyanate, and a low molecular weight polyol, the reaction product being further reacted with an amine curing agent.

[0061] Aspect 6. The chemical mechanical polishing pad of any one of aspects 1 to 5, wherein the isocyanate prepolymer comprises a blend of a first reaction product of polypropylene glycol, toluene diisocyanate, and a low molecular weight polyol and a second reaction product of polytetramethylene glycol, toluene diisocyanate, and a low molecular weight polyol, the first reaction product and the second reaction product being present in a weight ratio of 1:20 to 1:1.

[0062] Embodiment 7. The chemical mechanical polishing pad of any one of embodiments 1 to 6, having a density of at least 1.1 grams per cubic centimeter.

[0063] Aspect 8. The chemical mechanical polishing pad of any one of aspects 1 to 7, further comprising grooves on a surface of the polishing layer.

[0064] Aspect 9. The chemical mechanical polishing pad of aspect 8, wherein the grooves are machined into the surface of the polishing layer.

[0065] Aspect 10. The chemical mechanical polishing pad of any one of aspects 1 to 9, wherein the non-reactive, non-swelling polymer particles are porous.

[0066] All ranges disclosed herein are inclusive of the endpoints, and the endpoints can be independently combined with each other (e.g., the range "up to 25% by weight, more specifically 5% to 20% by weight" includes the endpoints and all intermediate values ​​in the range "5% to 25% by weight", etc.). Additionally, the upper and lower limits listed can be combined to form ranges (e.g., "at least 1% by weight or at least 2% by weight" and "up to 10% by weight or 5% by weight" can be combined to form the ranges "1 to 10% by weight" or "1 to 5% by weight" or "2 to 10% by weight" or "2 to 5% by weight").

[0067] The present disclosure can either comprise, consist of, or consist essentially of any suitable components disclosed herein. The present disclosure can additionally or alternatively be formulated to be free or substantially free of any components, materials, ingredients, adjuvants, or species used in prior art compositions or that are not necessary to achieve the function and purpose of the present disclosure.

[0068] All cited patents, patent applications, and other references are incorporated herein by reference in their entirety, except that if a term from an incorporated reference conflicts or conflicts with a term in this application, the term in this application takes precedence over the conflicting term in the incorporated reference.

[0069] Unless otherwise specified herein, all test standards are the latest standards in effect as of the filing date of this application or, if priority is claimed, as of the filing date of the earliest priority application in which the test standard appears. [Explanation of symbols]

[0070] 10 Substrate / Cavity 11 Features 20 Porous polishing pad 21 Pore 22 Matrix Polymer 30 Polishing pad containing polymer beads 31 31 Polymer Beads 50 Crescent Gap 60 Polymer Beads 70 Polymer Matrix 80 Expandable polymer microspheres 90 Residual Shell

Claims

1. 1. A chemical mechanical polishing pad having an abrasive layer, the abrasive layer comprising a matrix polymer, 1-20 wt. % non-reactive non-expanding polymer particles dispersed in the matrix polymer, and less than 2 wt. % expandable polymer microspheres, based on the total weight of the abrasive layer, wherein an SEM of a cross-section of the abrasive layer shows a crescent-shaped opening adjacent to and separating a surface of at least a portion of the polymer particle from the matrix polymer.

2. 10. The chemical mechanical polishing pad of claim 1, wherein the non-reactive non-swelling polymer particles comprise crosslinked polymethyl methacrylate.

3. 2. The chemical mechanical polishing pad of claim 1, wherein the non-reactive non-swelling polymer particles have an average particle size D50 particle size of 5 to 15 microns.

4. The chemical mechanical polishing pad of claim 1 , wherein the matrix polymer is ductile.

5. 2. The chemical mechanical polishing pad of claim 1, wherein the matrix polymer is a polyurethane comprising the reaction product of an isocyanate-terminated prepolymer and an amine curing agent, the isocyanate-terminated prepolymer comprising the reaction product of a polyol prepolymer, toluene diisocyanate, and a low molecular weight polyol, the reaction product being further reacted with an amine curing agent.

6. 6. The chemical mechanical polishing pad of claim 5, wherein the isocyanate prepolymer comprises a blend of a first reaction product of polypropylene glycol, toluene diisocyanate, and a low molecular weight polyol, and a second reaction product of polytetramethylene glycol, toluene diisocyanate, and a low molecular weight polyol, the first reaction product and the second reaction product being present in a weight ratio of 1:20 to 1:

1.

7. 10. The chemical mechanical polishing pad of claim 1 having a density of at least 1.1 grams per cubic centimeter.

8. The chemical mechanical polishing pad of claim 1 , further comprising grooves in a surface of the polishing layer.

9. The chemical mechanical polishing pad of claim 8 , wherein the grooves are machined into the surface of the polishing layer.

10. The chemical mechanical polishing pad of claim 1 , wherein the non-reactive, non-swelling polymer particles are porous.

Citation Information

Patent Citations

  • Polishing pads and methods for their use

    US5489233A